Role of multiple environmental stimuli in control of transcription from a nitrogen-regulated promoter in Escherichia coli with weak or no activator-binding sites. - Schneider, B L (1991)
Nitrogen regulator I (NRI [or NtrC])-phosphate stimulates transcription from the glnAp2 promoter of the glnALG operon in enteric bacteria. Unlike most activators, NRI-phosphate can stimulate transcription without apparent activator binding sites. We observed that when lacZ was controlled by a minimal glnAp2 promoter (without NRI binding sites) in Escherichia coli, lacZ expression was regulated by two different stimuli, the nitrogen status of the medium and the particular amino acid used as a nitrogen source. The latter stimulus did not affect the activity of the wild-type glnAp2 promoter, which has two high-affinity NRI binding sites. We present several lines of evidence that suggest that the concentration of NRI-phosphate limits the activity of the minimal glnAp2 promoter in vivo. Our results also suggest that nitrogen regulator II-dependent phosphorylation of NRI cannot account for the proposed variations in the concentration of NRI-phosphate. Therefore, to account for the regulation of the minimal glnAp2 promoter by two environmental stimuli, we propose that at least two protein kinases phosphorylate NRI during nitrogen-limited growth. We isolated and characterized mutants in which NRI could not stimulate transcription from the minimal glnAp2 promoter but could activate transcription from the wild-type glnAp2 promoter. These mutants could not utilize arginine or proline as a nitrogen source, suggesting that degradation of some nitrogen sources may require transcription from promoters similar to the minimal glnAp2 promoter.